DIPG-36. ANTI-GD2 CHIMERIC ANTIGEN RECEPTOR T CELLS AS A POTENT IMMUNOTHERAPY REGIMEN IN XENOGRAFT MODELS OF HISTONE 3 K27M MUTANT DIFFUSE MIDLINE GLIOMA. Issue 2 (22nd June 2018) - Mount, Christopher; Majzner, Robbie; Sundaresh, Shree; Arnold, Evan; Kadapakkam, Meena; Haile, Samuel; Labanieh, Louai; Woo, Pamelyn; Rietberg, Skyler; Vogel, Hannes; Monje, Michelle; Mackall, Crystal
Abstract: Diffuse intrinsic pontine glioma (DIPG) and other histone H3 K27M (H3K27M) mutated diffuse midline gliomas (DMGs) are aggressive and universally fatal pediatric brain cancers. Chimeric antigen receptor (CAR)-expressing T-cells have mediated impressive clinical activity in B-cell malignancies, and recent results suggest benefit in CNS malignancies. Here, we report that patient-derived H3K27M-mutant glioma cell cultures exhibit uniform, high expression of the disialoganglioside GD2. Anti-GD2 CAR T-cells incorporating a 4-1BBz costimulatory domain demonstrated robust antigen-dependent cytokine generation and DMG cell killing in vitro. In five independent patient-derived H3K27M+ DMG orthotopic xenograft models, systemic administration of GD2-CAR T-cells cleared engrafted tumors, save a small number of residual GD2-low glioma cells. Using a fluorescently-labeled GD2-CAR, we demonstrate tumoricidal GD2-CAR T cells infiltrating the brain parenchyma and sparing of local neurons during tumor clearing. While GD2-CAR T-cell administration was tolerated in the majority of animals, peri-tumoral neuroinflammation during the acute phase of antitumor activity resulted in hydrocephalus that was lethal in a fraction of animals. Similar swelling in thalamic xenograft models is lethal in a significant fraction of animals, presumably due to third ventricular compression and lethal transtentorial herniation. Given the precarious neuroanatomical location of midline gliomas, careful monitoring and aggressive neurointensive care management will be required for human translation. With a cautious multidisciplinary clinical approach, GD2-CAR T-cell therapy for H3K27M+ diffuse gliomas of the pons, thalamus and spinal cord could prove transformative for these lethal childhood cancers.